THEMATIC MAPPING OF LANDSLIDE SUSCEPTIBILITY IN NUEVA VIZCAYA: ENHANCING DISASTER RESILIENCE AND MANAGEMENT STRATEGIES - Raspado, Sarilyn B; Cid-Andres, Abigail P (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The province of Nueva Vizcaya had experienced landslide occurrences almost every year for the past decade, and last year, the municipality of Ambaguio had experienced landslides causing seven deaths, damages to properties, and degradation of environment. This study aimed to map the causative factors of landslide susceptibility in the municipality of Ambaguio, province of Nueva Vizcaya. The purpose of this study is to provide significant information to the Local Government Unit particularly the Municipal Disaster Risk Reduction and Planning Office, to mitigate disasters brought by landslides. The Geographic Information System and Analytical Hierarchy Process tools were utilized for the thematic mapping and weighting, respectively. The vulnerability of landslide was classified into four classes, namely low, moderate, high, and very high susceptibility. The total area of coverage in hectares in each susceptibility class was also determined to map the individual causative factors. The study reveals that slope, soil type, elevation, precipitation, and landcover with relative weights of 24.68%, 18.00%, 15.07%, 14.49%, and 10.89%, respectively, were the most influential factors of landslide susceptibility, whereas distance from roads and rivers with relative weights of 9.99% and 6.87%, respectively were identified as the least influential factors contributing to landslide susceptibility. To avoid reoccurrences of landsliding, reforestation and preservation of the ecosystem is highly recommended. Policies for land utilization and management for disaster risk reduction to be considered by the concerned authority are enforcement of slope-based zoning regulations, promotion of reforestation and forest conservation, adaptation of sustainable farming practices, development of a community-based landslide early warning system, and integration of disaster risk reduction in local land use and development planning.